Metanephric adenoma: Management in a 7-year-old child - Katharine Caldwell; Jason Wilson; Cynthia Reyes (Elsevier, 2015)
We report the case of a 7-year-old girl in whom a left renal mass was incidentally discovered on computerized tomography (CT) scan during evaluation for acute perforated appendicitis. The presence of polycythemia and the radiographic characteristics of the mass suggested a metanephric adenoma but a Wilm's tumor could not be excluded with preoperative studies. Gross inspection and intra-operative ultrasound of the tumor supported the suspicion of a metanephric adenoma and a partial nephrectomy was performed. Frozen section and permanent pathologic analysis confirmed a benign metanephric adenoma. At current date, patient is recovering well and polycythemia has resolved. A review of the management of metanephric adenoma in the child is presented.